1972
DOI: 10.1111/j.1755-3768.1972.tb03785.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Relatives of Patients With Glaucoma Simplex and Patients With Pseudoexfoliation of the Lens Capsule

Abstract: The occurrence of glaucoma and pseudoexfoliation of the lens capsule was investigated in 185 relatives, aged over 40, of patients with glaucoma simplex, glaucoma capsulare and normotensive pseudoexfoliation. The aggregate frequency of glaucoma and suspected glaucoma in the first group was 49, in the middle group 33 and the last group 9O/o. Pseudoexfoliation of the lens capsule was seen in 3 O i o of the glaucoma simplex relatives and 8 O / o of the pseudoexfoliation relatives. The genetic aspects of the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1973
1973
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…In an Icelandic twin study, five of eight monozygotic twins with exfoliation were concordant for ES with their cotwin, supporting the role of genetics in the aetiology underlying ES (Gottfredsdottir et al 1999). A few studies (Tarkkanen 1962;Pohjanpelto & Hurskainen 1972;Aasved 1975;Damji et al 1999;Allingham et al 2001;Orr et al 2001) in families consisting of between two and four generations have been described. Depending upon the study material, different modes of inheritance have been suggested: autosomal dominant (Tarkkanen 1962;Aasved 1975;Orr et al 2001), autosomal recessive (Andersen et al 1997) and maternal transmissions such as X-linked, mitochondrial and autosomal inheritance with genomic imprinting (Damji et al 1999).…”
Section: Introductionmentioning
confidence: 92%
“…In an Icelandic twin study, five of eight monozygotic twins with exfoliation were concordant for ES with their cotwin, supporting the role of genetics in the aetiology underlying ES (Gottfredsdottir et al 1999). A few studies (Tarkkanen 1962;Pohjanpelto & Hurskainen 1972;Aasved 1975;Damji et al 1999;Allingham et al 2001;Orr et al 2001) in families consisting of between two and four generations have been described. Depending upon the study material, different modes of inheritance have been suggested: autosomal dominant (Tarkkanen 1962;Aasved 1975;Orr et al 2001), autosomal recessive (Andersen et al 1997) and maternal transmissions such as X-linked, mitochondrial and autosomal inheritance with genomic imprinting (Damji et al 1999).…”
Section: Introductionmentioning
confidence: 92%
“…Genetic factors are now considered as predisposing factors for PES, although results are not clear and studies are still ongoing [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some genes may act as susceptibility factors that allow other genes or environmental influences to produce PEX. Further, familial aggregation and the increased frequency of PEX in relatives of affected subjects compared with relatives of unaffected subjects [36,37] suggest an underlying genetic component [38]. The main problems with studies on the genetic background of PEX have been the asymptomatic nature of PEX and late age of onset which make it difficult to collect multi-generation families with several affected individuals for linkage and association studies.…”
Section: Introductionmentioning
confidence: 99%